2011
DOI: 10.1177/0269215511423269
|View full text |Cite
|
Sign up to set email alerts
|

Effects of comprehensive geriatric assessment and targeted intervention on mobility in persons aged 75 years and over: a randomized controlled trial

Abstract: The comprehensive geriatric assessment and individually tailored multifactorial intervention had a positive effect on mobility, underlining their importance in health promotion and disability prevention in older people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…This study is part of a larger project, Geriatric Multidisciplinary Strategy for the Good Care of the Elderly (GeMS), which is a population-based intervention study that evaluated the effects of annual geriatric assessment and optimization of care (Lihavainen et al, 2011). A population-based sample of 1000 people aged !75 years who lived in Kuopio, Finland was invited and randomized into an intervention (n = 500) and control group (n = 500).…”
Section: Participantsmentioning
confidence: 99%
“…This study is part of a larger project, Geriatric Multidisciplinary Strategy for the Good Care of the Elderly (GeMS), which is a population-based intervention study that evaluated the effects of annual geriatric assessment and optimization of care (Lihavainen et al, 2011). A population-based sample of 1000 people aged !75 years who lived in Kuopio, Finland was invited and randomized into an intervention (n = 500) and control group (n = 500).…”
Section: Participantsmentioning
confidence: 99%
“…Multiple studies have evaluated the impact of physical function interventions and have been shown to improve a variety of outcomes including mobility, 16,17 strength, 18 balance, 19 gait speed 19,20 and decrease risk of falls. 21 Focused nutritional interventions have demonstrated improvement in Mini-Nutritional Assessment (MNA) scores and serum albumin levels.…”
Section: Introductionmentioning
confidence: 99%
“…"), while others assessed the need for help with walking (e.g., "Do you need special equipment or aids to help you with walking?"). Table 4 lists all standardized instruments for mobility limitation that were found Bannerman et al, 2002;Boudreau et al, 2009;Cappola et al, 2003;Cesari et al, 2005Cesari et al, , 2012Chaves et al, 2002;Davison et al, 2002;Fredman et al, 2008;Gray et al, 2011;Hardy et al, 2010Hardy et al, , 2011Hoffman et al, 2007;Houston et al, 2009Houston et al, , 2013Jylha et al, 2001;Keeler et al, 2010;Kim et al, 2010;Koster et al, 2005Koster et al, , 2007Koster et al, , 2008; Lee et al, 2005;Leveille et al, 2007;Lihavainen et al, 2012;Manini et al, 2007Manini et al, , 2009<...>…”
Section: Instrument Characteristics According To the Type Of Mobilitymentioning
confidence: 99%